Flavonol‐containing phosphorylated pullulan may attenuate pulp inflammation. (7th July 2012) - Yonehiro, J.; Yoshida, Y.; Yamashita, A.; Yoshizawa, S.; Ohta, K.; Kamata, N.; Okihara, T.; Nishimura, F.
Abstract Aim To find possible reagents to minimize inflammatory responses by using an established pulpitis models for the purpose of developing new pulp‐capping materials, and to test the possible use of phosphorylated pullulan as a carrier for such an anti‐inflammatory reagent. Methodology Co‐culturing was performed using transwell systems. Inflammatory responses were evaluated by measuring cytokines produced by the cells. The effects of two flavonoids, luteolin and quercetin, as anti‐inflammatory reagents, and phosphorylated pullulan, which potentially achieves a sufficient marginal sealing to hydroxyapatite and slowly releases luteolin, as a carrier for flavonoids, were tested. Results Flavonols, particularly luteolin, dramatically attenuated inflammatory cytokine production, which was augmented by co‐cultures. Luteolin was successfully enclosed by phosphorylated pullulan. Finally, it was confirmed that luteolin released from phosphorylated pullulan was effective in reducing cytokine production by co‐cultures. Conclusions Combination of phosphorylated pullulan and luteolin could be potentially used in the treatment of dental pulp inflammation.